Usability Evaluation and Recommendation For It Change Web Application By Using User Centered Design Method - Rafi, Aldilla; Kania Sabariah, Mira; Adrian, Monterico (eProceedings of Engineering, 2023)
Abstract— User interface is an important component of software because it acts as an intermediary between machines and humans. The user interface is a means of communication between the user and the program. In this case a dialogue is created between the program and the user so that the expert system can receive instructions and information (input) from the user. The program provides information (output) to the user. In Telkom Indonesia IT change is a Web Application that is used to initiate, compile, and submit as a basis for a change request which includes the addition, replacement, or deletion of objects in the production environment. IT Change Web Application in ITGC Compliance Division at Telkom Indonesia Bandung has constraints on UI / UX. In IT Change still does not have applied the concept of modern UI / UX based on user centered design and its only have a deployment and process flow. To solve problems from the Web Application IT Change will use the UCD (user centered design) method and for the pre-survey will use questionnaires and interviews, the results of the questionnaire are based on usibility testing using the system usability scale (sus).Key Word— User-centered Design, User Interface, Usability testing, System Usability Scale